Interventions to increase the consumption of water among children: A systematic review and meta‐analysis. (13th March 2020) - Franse, Carmen B.; Boelens, Mirte; Fries, Lisa R.; Constant, Florence; van Grieken, Amy; Raat, Hein
Summary: The aim of this study was to conduct a systematic review and meta‐analysis on the effectiveness of interventions to increase children's water consumption. A systematic literature search was conducted in seven electronic databases. Studies published in English before 18 February 2019 that evaluated any type of intervention that measured change in water consumption among children aged 2 to 12 years by applying any type of design were included. Of the 47 interventions included in the systematic review, 24 reported a statistically significant increase in water consumption. Twenty‐four interventions (17 randomized controlled trials and seven studies with other controlled designs) were included in the meta‐analysis. On average, children in intervention groups consumed 29 mL/d (confidence interval [CI] = 13–46 mL/d) more water than did children in control groups. This effect was larger in eight interventions focused specifically on diet (MD = 73 mL/d, CI = 20–126 mL/d) than in 16 interventions focused also on other lifestyle factors (MD = 15 mL/d, CI = 1–29 mL/d). Significant subgroup differences were also found by study setting and socioecological level targeted but not by children's age group, intervention strategy, or study design. In conclusion, there is evidence that, on average, lifestyle interventions can lead to small increases in children's daily water consumption. More research is needed to further understand the specific intervention elements that have the greatest effect.